TINDAK TUTUR ASERTIF DAN EKSPRESIF DALAM NOVEL BUMI KARYA TERE LIYE - Nurdiansyah, Redho; Patriantoro, Patriantoro; Muzammil, Ahmad Rabi’ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe researcher chose assertive and expressive speech acts in the Bumi novel written by Tere Liye. The research aimed to describe the form and function of assertive and expressive speech acts and describe the implementation plan of speech act for learning in the schools. The research problem was the form and function of assertive and expressive speech acts in the Bumi novel by Tere Liye. The research purpose was to describe the form and function of assertive and expressive speech acts in the Bumi novel by Tere Liye and describe the implementation plan of assertive and expressive speech acts learning in schools. The method used in this research was descriptive. The research used a qualitative research form. The data source in this study was the Bumi novel by Tere Liye. Research result in form of assertive and expressive speech acts, there 92 speech acts. Pragmatics also examines the meaning of speech and the meaning of context and analytical approaches in linguistics, including context considerations in language studies. Future researchers can either choose other types of speech acts as a focus of research or choose other research objects when choosing assertive and expressive speech acts.Key words: Assertive speech act, expressive speech act, novel